Diabetes Foot Exercises Using Tennis Balls To Reduce Elderly Blood Sugar Diabetes - abdurrasyid abdurrasyid (International Journal of Nursing and Health Services (IJNHS), 2020)
Uncontrolled blood sugar is a health problem that tends to occur in elderly type 2 diabetes mellitus (T2DM). Efforts to control blood sugar can be done with disease management activities, namely diabetes foot exercises. Elderly people who have diabetes mellitus are recommended to exercise in the form of diabetic foot exercises. The purpose of this study is to provide an overview of the effects of diabetic foot exercises using tennis balls in reducing blood sugar in T2DM elderly without a control group. Foot exercises using tennis balls were carried out in 58 elderly people with T2DM in Cisalak Pasar Village, Depok. The implementation of foot exercises using tennis balls is done for 30-60 minutes per session / week, as many as 12 sessions. The results of the implementation showed reduce blood sugar level ??of 5.1%. It can be concluded that leg exercises using tennis balls have an effect on reducing blood sugar in elderly with T2DM (p value <0.05; CI 95%). This intervention can be a form of intervention that can be provided in preventive health care for T2DM elderly clients